Bay Lodyans : Haitian Popular Film Culture. SUNY series, Afro-Latinx Futures - Accilien, Cécile; hoopla digital ([United States] : State University of New York Press, 2023)
In Haitian Creole, bay lodyans means to tell stories to an audience, and more generally, to entertain. This book is the first to analyze popular contemporary Haitian films, looking especially at how they respond to the needs and desires of Haitian audiences in and beyond Haiti. Produced between 2000 and 2018 and largely shot with digital cameras and sometimes cellphones, these films focus on the complexities of community, nostalgia, belonging, identity, and the emotional landscapes of exile and diaspora. They reflect sociopolitical and cultural issues related to family, language, im/migration, religion, gender, sexuality, and economic hardship. Using storytelling and other less traditionally "academic" techniques, Cécile Accilien advances Haitian epistemological frameworks. Bay Lodyans integrates terms and concepts from Haitian culture, such as jerans and kafou (derived from the French words for "to manage" and "crossroads," respectively) and includes interviews with Haitian filmmakers, actors, and scholars in order to challenge the dominance of Western theoretical approaches and perspectives.
Description based on online resource.
JSTOR
Keywords: Motion pictures -- Haiti; Haitians in motion pictures; Motion picture producers and directors -- Haiti; Motion picture industry -- Haiti; Haitian diaspora; Criticism; Performing arts; Video recordings; Electronic books; Critique; Cinéma.; Arts du spectacle; Vidéos.; Livres numériques.; Cinéma -- Haïti.; Producteurs et réalisateurs de cinéma -- Haïti.; Cinéma -- Industrie -- Haïti.; Haïtiens -- Pays étrangers.; performing arts (discipline); video recordings (physical artifacts); e-books.